Synthesizing a ν=2/3 fractional quantum Hall effect edge state from counter-propagating ν=1 and ν=1/3 states - Cohen, Yonatan; Ronen, Yuval; Yang, Wenmin; Banitt, Daniel; Park, Jinhong; Heiblum, Moty; Mirlin, Alexander D.; Gefen, Yuval; Umansky, Vladimir (Nature communications, 2019)
Topological edge-reconstruction occurs in hole-conjugate states of the fractional quantum Hall effect. The frequently studied filling factor, ν = 2/3, was originally proposed to harbor two counter-propagating modes: a downstream v = 1 and an upstream v = 1/3. However, charge equilibration between these two modes always led to an observed downstream v = 2/3 charge mode accompanied by an upstream neutral mode. Here, we present an approach to synthetize a v = 2/3 edge mode from its basic counter-propagating charged constituents, allowing a controlled equilibration between the two counter-propagating charge modes. This platform is based on a carefully designed double-quantum-well, which hosts two populated electronic sub-bands (lower and upper), with corresponding filling factors, v l and v u . By separating the 2D plane to two gated intersecting halves, each with different fillings, counter-propagating chiral modes can be formed along the intersection line. Equilibration between these modes can be controlled with the top gates’ voltage and the magnetic field. The boundaries of fractional quantum Hall states can host multiple, interacting one-dimensional edge modes, which test our understanding of strongly interacting systems. Here the authors observe the edge-mode equilibration transition that was predicted for the ν =2/3 fractional quantum Hall state.